(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
This paper explores the concepts of ’Being’ and ’Doing’ and is based on my workshop at the SEA 2015 conference, ’Being & Doing’. Can we separate the meaning of ’being’ and ’doing’? While many people will see a clear difference it seems that for existential philosophy ’being’ is fundamentally an activity, a ’doing’: both Martin Heidegger and Jean-Paul Sartre attempted to put a philosophy of ’Being’ into political action/doing. This paper will explore these issues and hopefully raise some important questions for existential therapists.